Using Journaling Techniques As A Method Of Expressing Feelings In Class 5 Students Of SDIT Qurthuba - Novita Maulidya Djalal; Anna Azizah; Andi Fatimah Azzahra; Alviyuniasticha IPRH (International Journal of Education, Vocational and Social Science, 2023)
Feelings are a condition that exists in human consciousness which is influenced by the knowledge possessed and is assessed as a negative and positive state. At the age of 11 years, children should be able to manage emotions and respond well to the expression of their emotions to others, know what is good and bad and the norms that are in force. This study aims to see an increase in the ability to channel feelings in fifth grade students at SD IT Qurthuba through journaling techniques. This research uses quantitative methods. This study has a subject of 20 people. Data collection techniques used in this activity were pretest and posttest questionnaires. The results of the study show that journaling techniques can improve the ability to channel feelings in fifth grade students.